Case Report: Uncommon presentation of Schistosoma haematobium infection in a migrant patient: diagnostic and therapeutic challenges - Francesca Carraturo; Maria Escolino; Assunta Russo; Angela Spagnuolo; Giovanni Esposito; Claudia Di Mento; Roberta Colicchio; Paola Salvatore; Paola Salvatore; Ciro Esposito; Mariateresa Vitiello (Frontiers in Medicine)
Schistosomiasis is a parasitic infection prevalent mainly in tropical and subtropical countries. We report a case of urinary infection caused by Schistosoma haematobium in a 16 years-old boy from Mali presented to our Institution with a one-month history of gross hematuria. The physical examination revealed an apparently healthy patient with soft abdomen, treatable, but painful to palpation and otherwise no other significant symptoms. The blood tests were within normal range except for eosinophilia. Urinary ultrasound revealed mild bilateral renal pelvis dilation, and distended bladder with thickened walls and multiple papillomatous growths (up to 31 mm in diameter). Cystoscopy confirmed multiple widespread mucosal lesions, and histology revealed severe eosinophilic cystitis with numerous parasitic eggs, observed, also, in parasitological urine examination, confirming the diagnosis of S. haematobium disease. The patient was diagnosed with schistosomiasis-related cystitis and treated with Praziquantel. At 2 months post-treatment follow-up urine microscope and eosinophil count were normalized and bladder wall irregularities and focal thickenings of variable size (from 3 to 11 mm) were documented. This case highlights the importance of considering hematuria and urinary bladder lesions in patients from areas where Schistosoma spp. is endemic as a strong indicator of parasitosis. Promptly initiating therapy can help prevent potential severe and less manageable consequences.